The characteristics of elderly patients seeking care at faculty of dentistry, chulalongkorn university during 2007-2009 and the development of dental service electronic database for the aged - Wiparat Youdying (Chulalongkorn University, 2012)
Thesis (M.Sc.)--Chulalongkorn University, 2011